Phytotoxicity stress induced by allelochemicals from foliar spray of Sida cordifolia methanol leaf extract on Ageratum conyzoides and Oryza sativa - Ahmed, Hassan; Juraimi, Abdul Shukor; Ahmad Hamdani, Muhammad Saiful; Omar, Dzolkhifli; Yusof, Mohammad Rafii (King Mongkut's Institute of Technology Ladkrabang, 2024)
Allelochemicals are key inhibitors that induce chemical stress in plants. Their mechanisms as agents of oxidative stress are not well understood. A field study was conducted to evaluate herbicidal potential of Sida cordifolia methanol leaf extract (SCLE) on Ageratum conyzoides and Oryza sativa (weedy rice). SCLE concentrations of 0, 3, 6 and 9 g L-1 were prepared and sprayed twice at 7 days interval. The results showed that the SCLE significantly (p<0.05) affected growth attributes, chlorophyll pigments, and proline, and catalase, superoxide dismutase and peroxidase enzyme activities in a concentration-dependent pattern. It was found that high concentrations of SCLE induced greater phytotoxicity against A. conyzoides compared to O. sativa. SCLE spraying stimulated production of reactive oxygen species, boosting their ability to cause damage and inhibit growth. The allelochemicals in the extract stimulated an increased in the level of proline, which is an indicator of oxidative stress. Understanding the physiological and biochemical responses to Sida extract can improve our knowledge on allelochemical target sites and help us to explicate the mechanisms of action of such compounds.